2018
DOI: 10.1007/s00261-018-1777-8
|View full text |Cite
|
Sign up to set email alerts
|

Renal solitary fibrous tumor/hemangiopericytoma: computed tomography findings and clinicopathologic features

Abstract: We have shown that rSFT/HPCs usually arise from the renal sinus, and present as lobulated, slightly hyperdense, gradually enhancing soft tissue masses. CT findings, including large size, heterogeneity, and the PE pattern, may assist in the pre-operative identification of malignant grade III rSFT/HPCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Primary neoplasms of the renal sinus are rare and can originate from any of the tissue elements present 1. Examples include angiomyolipoma, anastomosing hemangioma, “myxoma,” solitary fibrous tumor, leiomyoma, lymphoma, immunoglobulin (Ig) G4–related disease, and well-differentiated/dedifferentiated liposarcoma 2–9. Myxoid lesions of the renal sinus, in particular, may present a diagnostic challenge because although myxoid liposarcoma occurring in the retroperitoneum is rare,10 well-differentiated liposarcoma with myxoid change is not infrequent in this location, including in perirenal soft tissue 11…”
mentioning
confidence: 99%
“…Primary neoplasms of the renal sinus are rare and can originate from any of the tissue elements present 1. Examples include angiomyolipoma, anastomosing hemangioma, “myxoma,” solitary fibrous tumor, leiomyoma, lymphoma, immunoglobulin (Ig) G4–related disease, and well-differentiated/dedifferentiated liposarcoma 2–9. Myxoid lesions of the renal sinus, in particular, may present a diagnostic challenge because although myxoid liposarcoma occurring in the retroperitoneum is rare,10 well-differentiated liposarcoma with myxoid change is not infrequent in this location, including in perirenal soft tissue 11…”
mentioning
confidence: 99%
“… 30 Amonst all stromal cells, CAFs are considered as the most important ones because of their abundance and their strong interaction with cancer cells. 7 , 35 CAFs were proven to promote the invasion and treatment resistance of cancer cells through paracrine and extracellular matrix (ECM) remodeling in many solid tumors including HNSCC, 36 , 37 , 38 , 39 , 40 however, the clinical significance of CAF‐related genes expression remains unclear. In our study, we identified two new HNSCC subtypes based on the 66 CAF‐related genes expression level obtained from TCGA database, while further consensus clustering analysis showed that the patients assigned to the cluster 1 had higher stromal infiltration and worst prognosis than the patients in the cluster 2.…”
Section: Discussionmentioning
confidence: 99%
“…The delayed enhancement may be related to the abundance of collagen fibers, which restrict the diffusion of contrast agent within the tumor. 4,20 Lane et al 15 found that MESTK commonly tends to extend into the renal sinus. In our study, 10 subjects (55.5%) have demonstrated SFI, indicating that nephron-sparing surgery is not the best management plan for such tumors compared to those without the SFI.…”
Section: Discussionmentioning
confidence: 99%
“…Gradual enhancement pattern was considered present when the tumor attenuation in the NP was at least 20 Hounsfield units (HU) greater than that in the CMP, 19 while gradual washout pattern was defined when the CT value of the subsequent phase was reduced to less than 20 HU. 20 The degree of enhancement was defined as the difference between the attenuation value of the unenhanced scan and the CMP. A difference higher than 50 HU was classified as marked, between 20 and 50 HU as moderate, and less than 20 HU as weak enhancement.…”
Section: Imaging Analysismentioning
confidence: 99%